FORMATION OF FOREIGN-LANGUAGE COMMUNICATIVE COMPETENCE OF FUTURE LAWYERS USING INTERACTIVE TECHNOLOGIES - Бухінська, Тетяна Вікторівна; Гладкоскок, Леся Григорівна; Мельник, Олена («Young Scientist», 2020)
Summary. In the article the peculiarities of formation of foreign language communicative competence among law students are analyzed. This competence is determined by the ability to communicate effectively in a foreign language in the conditions of a foreign language environment. The components, which reflect the content of the foreign language communicative competence and correspond to the purposes of teaching foreign language students of legal specialties, are distinguished. The focus is on the ways of integrating the set of innovative methods and technologies of foreign language learning, as well as on the organization of a holistic educational process based on competency and communication approaches.
ФОРМУВАННЯ ІНШОМОВНОЇ КОМУНІКАТИВНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНІХ ЮРИСТІВ З ВИКОРИСТАННЯМ ІНТЕРАКТИВНИХ ТЕХНОЛОГІЙ
Keywords: competence; communicative approach; professional communication; foreign languages; teaching methods; interactive technologies.